Clinical Manifestations and Behavior Changes in Rats Treated with Jamaican Cherries Extract (Muntingia calabura) - Afdhaliya, Noor Khalwati; Indarto, Dono; Wasita, Brian (Universitas Aisyah Pringsewu, 2022)
Iron deficiency anemia (IDA) in female adolescents is one of the health problems, which occupied 8th position as a cause of global disability and is the main cause of anemia in reproductive women. Iron tablet supplementation is the government program to reduce IDA prevalence in Indonesia but often results in gastrointestinal side effects. Jamaican cherries fruits contain vitamin C, iron and flavonoids, which play essential roles in iron metabolism. This study aimed to investigate the effects of Jamaican cherries fruits ethanol extract on clinical manifestations and behavior changes in female Wistar rats. This randomized controlled trial with pre-posttest control group design used 24 female Wistar rats, aged 10 -12 weeks and were randomly divided into 6 groups: N, positive control (PC: AIN-93M low iron food + elemental iron) and treatments (T1-4: AIN-93M low iron food + 0.26, 0.35, 0,5 or 0.75g/ 100g Body Weight (BW) Jamaican cherries fruits extract respectively for 28 days). Clinical manifestations, reflexes and behavior changes were observed at day 0, 14 and 28 interventions. BW data were analyzed using one way ANOVA and repeated measures ANOVA tests. All rats had normal reflexes and did not show clinical manifestations and behavior changes. The average of rat BW in T1-4 groups did not significantly differ before (p=0.896), during (p=0.884) and after treatment (p=0.775) but the average of rat BW in the T1 group increased significantly (p=0.012). In conclusion, administering Jamaican cherries fruits ethanol extracts up to 0.75g/100g BW has no toxic effects in female Wistar rats. Abstrak: Anemia defisiensi besi (ADB) pada remaja putri merupakan salah satu masalah kesehatan yang menempati posisi ke-8 sebagai penyebab disabilitas tingkat global dan penyebab utama anemia pada ibu hamil. Suplementasi tablet besi merupakan program pemerintah untuk mengurangi prevalensi ADB di Indonesia tetapi sering menimbulkan efek samping di saluran percernaan. Buah kersen mengandung vitamin C, zat besi dan flavonoids yang berperan penting dalam metabolisme besi. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak buah kersen terhadap manifestasi klinis dan perubahan perilaku tikus Wistar betina. Penelitian randomized controlled trial ini dengan pre-posttest control group design dengan menggunakan 24 ekor tikus Wistar betina umur 10 -12 minggu dan dibagi secara acak menjadi 6 kelompok: normal, kontrol posistif (KP) dan perlakuan (P1-4). Tikus di KP diberi pakan AIN-93M dengan besi rendah + besi elemental sedangkan P1-4 diberi pakan yang sama ditambah 0.26, 0.35g, 0,5g atau 0.75g/100g berat badan (BB) secara berturut-turut ekstrak buah kersen selama 28 hari. Manifestasi klinis, reflek dan perubahan perilaku tikus diamati pada hari ke-0, 14 dan 28. Data BB dianalisis menggunakan uji one way ANOVA dan uji repeated measures ANOVA. Semua tikus memiliki reflek yang normal dan tidak menunjukkan manifestasi klinis dan perubahan perilaku. Rerata BB tikus pada P1-4 tidak berbeda signifikan sebelum (p=0,896), selama (p=0,884), maupun setelah perlakuan (p=0,775) tetapi rerata BB tikus P1 meningkat secara signifikan (p=0,012). Kesimpulan, pemberian ekstrak buah kersen hingga 0,75g/100g BB tidak menyebabkan toksisistas tikus Wistar betina.